Implications of nutritional status in patients on hemodialysis: A narrative review (Research, Society and Development, 2021)
The prevalence of chronic kidney disease (CKD) has increased considerably in recent years, involving in its course a series of complications resulting from metabolic and inflammatory changes that lead to important nutritional disorders, as well as an imbalance in the antioxidant defense. Careful assessment of nutritional status is essential for planning interventions that effectively meet the nutritional needs of patients with this pathology. Thus, the present study aimed to identify the main implications of nutritional status related to CKD in patients undergoing hemodialysis, listing the best nutritional diagnosis methods and their relationship with the increase in oxidative stress. This is a narrative review of the literature in which the following descriptors were used: Nutritional Therapy, Chronic Kidney Disease, Hemodialysis and Oxidative Stress. The search was carried out through research with studies from the last 20 years comprising the period from January 2001 to May 2021, in the Pubmed, Scielo and Capes Periodical databases, using the original articles that were found relevant to the study and that addressed the theme. As noted, most of the time, the renal patient is malnourished, with a lack of vitamin and mineral reserves, which reduces the antioxidant defense mechanisms and favors the installation of renal oxidative stress, forming reactive species of oxygen metabolism. Substances that are potentially harmful to the body. Thus, it can be stated that chronic kidney patients have significant nutritional deficiencies, requiring constant monitoring of their nutritional status as it is a strong predictor of morbidity and mortality.